Investigation of soil contaminated with Toxoplasma gondii oocyst in urban public environment, in Brazil. (December 2021) - de Oliveira, Pollyanne Raysa Fernandes; de Melo, Renata Pimentel Bandeira; Sierra, Tania Alexandra Ortega; da Silva, Renato Amorim; da Silva de Oliveira, José Eudes; de Almeida, Brivaldo Gomes; Mota, Rinaldo Aparecido
Abstract: In this study, we determined the occurrence of Toxoplasma gondii oocysts in soil samples from public places. A total of 120 samples were collected from 24 sites, including squares, parks, university, hospitals in the city of Recife. The recovered oocysts were subjected to a nested-PCR test, and nine sites (9/24) were found to be positive for gene of apicomplexan parasites. The PCR product was sequenced, and 8.33% (10/120) of the samples showed 100% similarity to T. gondii DNA. T. gondii oocysts were detected in 75% (3/4) of the evaluated hospital soil samples and in 23.81% (5/21) soils samples from the public squares and parks. The results of this study demonstrate the potential of the soil in the areas analyzed as a source of T. gondii infection and therefore highlight the importance of devising educational strategies on the use of these sites, in addition to future cleaning protocols in public areas. Highlights: Molecular detection of Toxoplasma gondii in public spaces. Physicochemical variables of the soil contaminated by Toxoplasma gondii oocysts. Public spaces as potential sources of parasite infection for susceptible hosts.